2018
DOI: 10.1371/journal.pone.0202336
|View full text |Cite
|
Sign up to set email alerts
|

Autism and the right to education in the EU: Policy mapping and scoping review of the United Kingdom, France, Poland and Spain

Abstract: IntroductionAutistic people may have different educational needs that need to be met to allow them to develop their full potential. Education and disability policies remain within the competence of EU Member States, with current educational standards and provisions for autistic people implemented locally. This scoping review aims to map EU and national special education policies with the goal of scoping the level of fulfilment of the right to education of autistic people.MethodsFour EU countries (United Kingdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 17 publications
6
34
0
Order By: Relevance
“…The place where the support services are delivered remains ambiguous because policies rarely explicitly state the place of delivery [12][13][14][15][16][17]. Parental involvement, however, was previously found to be key in letting children with SEN experience effective and welcoming educational settings in which their needs are met [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The place where the support services are delivered remains ambiguous because policies rarely explicitly state the place of delivery [12][13][14][15][16][17]. Parental involvement, however, was previously found to be key in letting children with SEN experience effective and welcoming educational settings in which their needs are met [5].…”
Section: Discussionmentioning
confidence: 99%
“…This study synthesizes the ndings of the policy analyses by EDUCAUS, which comprises descriptive data on individual policies of the 20 investigated EU Member States [12][13][14][15][16][17]. Information in each case was collected by means of a scoping review [28,29] of the respective national policy repository and analyzed through a path dependence analysis [30].…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The census is conducted in each of the four countries that make up the United Kingdom, and data is now available over a nine‐year period for the school years 2010/11 to 2018/19. Moreover, the four countries have enacted legislation specific to autism and have issued policy guidance on special educational needs provision (Roleska et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The widely accepted Universal Declaration of Human Rights proclaimed in 1948 that everyone has the right to work and the right for protection against unemployment [United Nations, 1948], making it a human rights problem on top of a public health challenge if people with autism are denied or obstructed (access to) employment. Analyses of special education policy for children with autism by the European Consortium for Autism Researchers in Education [EDUCAUS, 2019] found that the right to education that was incorporated in the UDHR was further elaborated on by other international documents and subsequently implemented in national policy [Roleska et al, 2018;van Kessel, Roman-Urrestarazu, et al, 2019;van Kessel, Walsh, et al, 2019]. As such, it can be expected that this is also the case for rights surrounding employment-even though this has not yet been comprehensively investigated yet.…”
Section: Introductionmentioning
confidence: 99%